PELATIHAN MEMBENTUK JIWA WIRAUSAHA YANG KOMPETITIF BAGI CALON DAN PELAKU UMKM TANGERANG - Dorina Widowati; Kurniawati; Mochammad Sabur; Prastiyo Diatmono (Jurnal Pengabdian Masyarakat Sabangka, 2025)
MSMEs play a vital role in accelerating economic recovery and employment. However, in a competitive market, aspiring and existing entrepreneurs need strong skills and entrepreneurial mindset. This community service program aimed to build a competitive entrepreneurial spirit among students of Bina Amanah Cordova School through a training session. The program included motivational content, practical strategies, and participatory discussion. Evaluation results showed improvements in understanding, confidence, and entrepreneurial ability.. This indicates the importance of such training to empower MSMEs for sustainable growth